Inovasi Pelayanan Publik di Daerah - Henri Prianto Sinurat; Rati Sumanti (Puslatbang KHAN, 2017)
Bureaucracy reform in the regions of Indonesia cannot be separated from innovation, since it is one of important strategies for the achievement of good governance. While, innovation has not become a culture for the government bureaucracy so that, extra effort is required. Based on its development, innovation has started to enhance in several areas in order to answer the obstacles and problems in the region. This research has mapped out the policy strategies, undertaken by the Provincial Government of South Sumatra and the government of East Belitung Regency in translating innovation as a better step in the delivery of public services. Using qualitative research method and data collection techniques focused discussions and interviews, several strategies were obtained in the locus area of the research. South Sumatra province constructs the nomenclature changes by inserting an innovation department at the Regional research and Development Agency to officially become the Regional Research, Development and Innovation Agency. The ultimate goal is able to facilitate and improve the science and technology of the innovation and technology in South Sumatra in order to be beneficial for the society. Meanwhile, Kampung Keluarga Berencana as a public innovation in East Belitung Regency has been socialized featuring its strategy, KB Pria Perkasa group. The socialization was held in coffee shops, aimed to increase the level of prosperity in society by developing prosperous families and family planning programmes.